2020
DOI: 10.3390/catal10111351
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Chemical Synthesis of Au/CeO2 Nanoparticle Catalysts for Room Temperature CO Oxidation: A Comparative Study

Abstract: In many heterogeneous catalytic reactions, such as low-temperature CO oxidation, the preparation conditions, and the role of the CeO2 support (oxygen vacancies and redox properties) in the dispersion and the chemical state of Au, are considered critical factors for obtaining gold nanoparticle catalysts with high catalytic performance. In this work, the physical and chemical preparation methods were compared, aiming at understanding how the preparation method influences the catalytic activity. The Au/CeO2 nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…31 But, because of the extremely low gold loading (only 0.3 wt%), the gold diffraction peaks are not clearly dened, which is also consistent with previous reports. 31,32 The small Au particles estimated by the Debye-Scherrer equation 33,34 with sizes of around 1 nm are considered to be below the XRD detection limit, 32 which suggests that Au nanoparticles were well dispersed on the surface as well as in the internal structure of the CeO 2 nanorods. 35 The XRD results also showed no interaction between AuNPs and CeO 2 to form a new phase.…”
Section: Characterization Of Catalystsmentioning
confidence: 99%
“…31 But, because of the extremely low gold loading (only 0.3 wt%), the gold diffraction peaks are not clearly dened, which is also consistent with previous reports. 31,32 The small Au particles estimated by the Debye-Scherrer equation 33,34 with sizes of around 1 nm are considered to be below the XRD detection limit, 32 which suggests that Au nanoparticles were well dispersed on the surface as well as in the internal structure of the CeO 2 nanorods. 35 The XRD results also showed no interaction between AuNPs and CeO 2 to form a new phase.…”
Section: Characterization Of Catalystsmentioning
confidence: 99%
“…Carbon monoxide is a common contaminant of hydrogen streams that poisons platinum-based catalysts of PEMFC type fuel cells [4]. For the CO oxidation reaction, catalysts based on noble metals such as Au, Pt, and Pd have traditionally been used [5][6][7], although among them, the most widely used systems have been those based on supported gold such as Au/ZnO-ZrO 2 , Au/CeO 2 , or Au/Co 3 O 4 -CeO 2 [8][9][10]. However, as mentioned above, the search for noble metals-free catalysts in recent years has led to the development of systems based on mono-and multi-metallic oxides.…”
Section: Introductionmentioning
confidence: 99%
“…The unique property of ceria provides more active lattice oxygen, increases the dispersion of the loaded metal and prevents sintering or coke formation. [25,26] Saoud et al [27] dispersed gold nanoparticles on CeO 2 and found that strong interaction between Au and CeO 2 leads to high CO oxidation ability even below room temperature. Lee et al [28] constructed a Rh-doped CeO 2 catalyst, which exhibited a remarkable soot oxidation activity owning to abundant surface oxygen vacancies and efficient electron transfer.…”
Section: Introductionmentioning
confidence: 99%